The effect of diet or exercise on ectopic adiposity in children and adolescents with obesity: a systematic review and meta‐analysis. (14th September 2017) - Hens, W.; Vissers, D.; Hansen, D.; Peeters, S.; Gielen, J.; Van Gaal, L.; Taeymans, J.
Summary: Objective: Ectopic fat depostion in youth with obesity is associated with an increased cardiovascular disease risk. The aim of this meta‐analysis was to summarize the evidence for the use of diet and/or exercise on ectopic adiposity in this population. Methods: A systematic literature search was performed according to the Preferred Reporting Items for Systematic Reviews and Meta‐analysis statement. Clinical trials that assessed ectopic fat deposition and included study arms with diet and/or exercise were searched in PubMed, PEDro and the Cochrane database. Results: Hepatic fat content and intramyocellular lipid content were described in nine studies and three studies, respectively. Most studies included teenagers, and study duration ranged between 3 and 12 months without follow‐up. Using random‐effects weights, the standardized mean difference of the change in hepatic adiposity (totalling 320 subjects) was −0.54 Hedges' g (95% confidence interval: −0.69 to −0.38 with p < 0.0001). By re‐expressing this effect size, it is seen that diet and/or exercise results in an absolute reduction of intrahepatic lipid with 2%, which accords with a relative reduction up to 70%. Although there were significant ameliorations of insulin sensitivity, no significant changes in intramyocellular lipid were observed. Conclusions: This meta‐analysis showed that diet and/or exercise is effective to reduce hepatic adiposity in youth with obesity.